THE STARS - Mcmullen, Gemma; Allatson, Amy; Rumbelow, Matt; McMullen, Ian (King's Lynn, Norfolk : The Secret Book Company, 2019)
This series explores the four key elements of our Solar System: The Sun, The Moon, The Planets and The Stars. With each title including fascinating facts and photographic images, young readers will enjoy what lies in the darkness beyond
The solar system -- What are stars -- The sun -- Sizes and colours -- Galaxies -- Constelations -- Astronomy -- Stargazing -- Shooting stars -- Super star! -- Glossary and index.
Includes index
Keywords: Stars -- Juvenile literature; Stars; Juvenile works; Juvenile literature